Pengaruh Diversifikasi Pendapatan Terhadap Profitabilitas dan Stabilitas Perbankan di Indonesia: The Impact of Income Diversification on Banking Profitability and Stability in Indonesia - Tiara Kusumadewi; Wita Juwita Ermawati; Tony Irawan (School of Business, Bogor Agricultural University (SB-IPB), 2024)
The global economic crisis that occurred during the COVID-19 pandemic causing credit contraction that negatively affected the banking industry. Previous studies have shown that diversifying the bank's income to non-interest sources able to rescue banks to overcome financial hardship in the crisis but very few studies have been conducted to measure the impact of crisis during COVID-19 pandemic on bank’s profitability and stability. This paper aims to investigates the dynamics and the impact of income diversification on banking profitability and stability in Indonesia uses statistic descriptive and panel data regression of 72 conventional banks grouped into business groups based on core capital during 2017-2021 period, along with bank-specific (cost to income, loan to deposit ratio, capital adequacy ratio, size) and macroeconomic (crisis dummy during COVID-19 pandemic) used as control variables. Based on statistic descriptive, BUKU 1 group's income diversification increased during the crisis but shown a low profitability and stability. BUKU 2 and BUKU 3 group’s stability increased during the crisis but income diversification and profitability decreased. BUKU 4 group has the finest income diversification approach for achieving great profitability and stability. Results of panel data regression show that income diversification have a positive impact on bank’s profitability and stability. Keywords: conventional bank, crisis during covid-19 pandemic, bank’s income diversification, bank’s profitability, bank’s stability